Pengaruh bauran pemasaran dan orientasi pasar terhadap keunggulan bersaing pada usaha waralaba di Kabupaten Oku - Yunita Sari; Angga Wibowo Gultom (Jurnal Akuntansi, Keuangan, dan Manajemen, 2019)
Purpose: This study aims to examine the effect of marketing mix (products, pries, distribution channels, promotions) and market orientation on competitive advantage of franchising (Alfamart and Indomaret) in Ogan Komering Ulu Regency. Research methodology: This study was survey research with a quantitative approach. The populations in this study were the Alfamart and Indomaret franchise businesses in OKU Regency. The analytical method used was multiple regression. Results: This study indicates that product, price, promotion, and market orientation variables have a positive and significant effect on the competitive advantage of franchising in OKU Regency, while the distribution channel variables have an insignificant effect Limitations: This research focuses on product, price, distribution channels, promotion and market orientation as independent variables; and the competitive advantage as dependent variable. Contribution: This research explains the competitive strategies that a business must have and also the implications of marketing management theory. Keywords: Marketing mix, Market orientation, Competitive advantage